Use of non-radioactive detection in SSCP, direct DNA sequencing and LOH analysis. Issue 2 (April 1996) - Petersen, I; Reichel, M B; Dietel, M
Abstract : Aims —To develop a protocol that is applicable to single strand conformation polymorphism (SSCP), direct sequencing and loss of heterozygosity analysis of DNA. Methods —The protocol is based on the detection of biotinylated DNA by a Streptavidin-alkaline phosphatase conjugate. Biotinylation of DNA was achieved by using 5′-end biotinylated primers for PCR. After polyacrylamide gel electrophoresis, the DNA fragments were transferred to a nylon membrane by contact blotting. Depending on the alkaline phosphatase substrate, DNA was visualised either colorimetrically or by chemiluminescence. Results —The method was verified by the identification and characterisation of p53 mutations by SSCP analysis and direct DNA sequencing, as well as the assessment of DNA loss in human lung carcinomas by microsatellite polymorphism allelotyping. Conclusions —The protocol is simple, does not require specialised equipment and would be particularly useful for laboratories with experience in Streptavidin-biotin methodology.